Radio Sensor for Monitoring of UMTS Mobile Terminals - Kozak, Filip; Hudec, Premysl (Společnost pro radioelektronické inženýrství, 2014)
Relatively simple and low-cost radio sensor for monitoring of 3rd generation (3G) UMTS mobile terminals (i.e., phones) has been designed and practically tested. The main purpose of this sensor is to serve as an extending module that can be installed into systems used for monitoring of standard 2nd generation (2G) GSM and DCS mobile phones in highly guarded buildings and areas. Since the transmitted powers of UMTS mobile terminals can be very low in relation to GSM and DCS specifications, the new UMTS sensor is based on a highly sensitive receiver and additional signal processing. The radio sensor was practically tested in several scenarios representing worst-case mobile terminal - base station relations. The measured detection ranges attain values from approx. 11 m inside of rooms to more than 30 m in corridors, which seems to be sufficient for the expected application. Results of all performed tests correspond fairly well with the presented theoretical descriptions. An extended version of the radio sensor can be used for monitoring of mobile terminals of all existing voice or data formats.
Keywords: Radio sensor; UMTS detection and monitoring; sensor network; security applications; 3G mobile phone.